Dos de Mayo theater (Chiclayo, Peru), 147 years later: Comprehensive study for its Value - Baldera Chávez, Anabel (2025)
The objective of this article is to identify and reflect on strategic aspects of the Dos de Mayo Theater, a heritage building in the city of Chiclayo, so that they can be considered in a future proposal for its enhancement, understanding its problems as part of the city, exposed and influenced during its 147 years. by constant urban dynamics related to technological inventions, fashions, migrations and cultural changes, among others. From visual inspection work, research in archives and digital sources on the Internet, interviews and personal communications with people linked to the historical study and management of performing arts in Chiclayo, the comprehensive study was completed that evidenced numerous findings that constitute a complex problem that far exceeds its obvious poor state of conservation.